Graphene Field‐Effect Transistors for the Sensitive and Selective Detection of Escherichia coli Using Pyrene‐Tagged DNA Aptamer. Issue 19 (10th August 2017) - Wu, Guangfu; Dai, Ziwen; Tang, Xin; Lin, Zihong; Lo, Pik Kwan; Meyyappan, M.; Lai, King Wai Chiu
Abstract: This study reports biosensing using graphene field‐effect transistors with the aid of pyrene‐tagged DNA aptamers, which exhibit excellent selectivity, affinity, and stability for Escherichia coli ( E. coli ) detection. The aptamer is employed as the sensing probe due to its advantages such as high stability and high affinity toward small molecules and even whole cells. The change of the carrier density in the probe‐modified graphene due to the attachment of E. coli is discussed theoretically for the first time and also verified experimentally. The conformational change of the aptamer due to the binding of E. coli brings the negatively charged E. coli close to the graphene surface, increasing the hole carrier density efficiently in graphene and achieving electrical detection. The binding of negatively charged E. coli induces holes in graphene, which are pumped into the graphene channel from the contact electrodes. The carrier mobility, which correlates the gate voltage to the electrical signal of the APG‐FETs, is analyzed and optimized here. The excellent sensing performance such as low detection limit, high sensitivity, outstanding selectivity and stability of the graphene biosensor for E. coli detection paves the way to develop graphene biosensors for bacterial detection. Abstract : The pyrene‐tagged DNA aptamer‐modified graphene field‐effect transistor biosensors are demonstrated for Escherichia coli ( E. coli ) detection with high sensitivity, selectivity, and affinity. The change of the carrier density in the probe‐modified graphene due to the attachment of E. coli is correlated with the electrical response of the graphene biosensors.